Asuhan Keperawatan Luka Pengaruh Efektifitas Zinc Cream Terhadap Penyembuhan Luka Diabetikum di PSBDBB 2 Cengkareng Jakarta Barat - Annisa Sukma Wianda Dwipa; Oryza Intan Suri (Jurnal Kesehatan STIKes Sumber Waras, 2025)
Background: Diabetes mellitus or diabetes is a hereditary disease whose incidence is increasing due to unhealthy lifestyles. It was found that 2% of the Indonesian population aged more than 15 years was diagnosed with Diabetes Mellitus. Uncontrolled Diabetes Mellitus will develop diabetic wound complications. Diabetic ulcers are wounds caused by nerve damage, blood vessel damage. It is caused by the blockage of small blood vessels which is the impact of peripheral vascular occlusive disease. Objective: To determine the effectiveness of Zinc Cream on diabetic foot wound care. Methods: Case studies were conducted on 2 respondents, the intervention provided was to perform foot wound care once for 7 consecutive days. Results: After the wound care intervention using Zinc Cream, there were changes in wound characteristics in both clients. Patient 1 showed a change in wound size from 14cmx10.5cm to 13.5cmx9cm, while patient 2 showed a change in size from 3.5cmx3.5cmx6cm with slough to 3cmx2.5cmx5cm without slough. This shows the effectiveness of Zinc Cream in overcoming the problem of diabetic foot wounds. Conclusion: having diabetes with foot wounds can be uncomfortable and wound care using Zinc Cream is effective in improving the appearance of wounds although results are influenced by the physical condition and characteristics of the wound.